Safeguarding rural-urban linkages: modeling drivers of peri-urban sprawl and impacts on ecosystem services - Dekolo, Samuel; Ekum, Matthew I.; James, Omobolanle K.; Aigbavboa, Clinton; Gumbo, Trynos (Frontiers in Sustainable Cities, 2025)
Africa is experiencing unparalleled urbanization, with projections suggesting that by 2030, more than 50% of its inhabitants will live in urban areas. Uncontrolled spatial expansion threatens sustainability, especially in megacities like Lagos. Urban sprawl in peri-urban areas has led to the loss of valuable agricultural lands, food security risks, and breaking the link between rural and metropolitan regions. This study investigates the proximate factors driving urban sprawl on statutory agricultural lands in peri-urban areas of Lagos. An interdisciplinary methodology that employs remote sensing, land change analysis, field surveys, and structural equation modeling was adopted. The findings revealed that built-up areas in the Ikorodu municipality increased by 127% over 32 years, leading to fragmented and uncontrolled development in statutory agricultural zones. The structural equation modeling for 322 homeowners sampled shows a lack of policy awareness and weak development control as major underlying drivers, explaining 37% of peri-urban expansion. Also, declining per capita arable lands indicate risks to regional food self-sufficiency. A strategic land management approach is needed to leverage rural–urban linkages that safeguard food provisioning services and achieve resilient African megacities. Also, rapidly growing African cities should adopt spatial planning incorporating agroecological perspectives and collaborative governance of urban and rural lands for a sustainable future.